Comparison of the content of Data display domain (TIMSS 2015) in Slovak and Singapore primary mathematics curriculum - Valentová, Lenka; Punčová, Alexandra (Technium Social Sciences Journal, 2020)
International benchmark assessments have been a measure of a success of an education system for several decades [1]. They provide data for evaluating the knowledge of students of different ages in the given subjects, and offer us a unique opportunity to compare the performance of students in the Slovak Republic with the performance of students in other countries of the world. The TIMSS (Trends in International Mathematics and Science Study) has monitored trends in mathematics and science achievement at the fourth and eighth grades since 1995. The latest released results of the study are from 2015. Each of assessment frameworks for TIMSS 2015 was organized around two dimensions: Content dimension (the subject matter) and Cognitive dimension (the thinking processes). In the Content dimension of mathematics, three content domains were assessed: Numbers, Geometric shapes and measures, and Data display. Slovak 10-year-old students achieved 492 points in TIMSS 2015 – Data display domain, which is incomparable with 600 points of Singapore 4th grade students [3]. In Slovakia, in addition to international testings, since 2015 the National Institute of Certified Educational Measurements (NICEM) [2] has also been organizing nationwide testings of 5th grade students – T5. In T5 from mathematics, five thematic units are represented, including The solution of application tasks and tasks developing specific mathematical thinking – which is comparable to the domain of the Data display in TIMSS. From the results (52,06 % in 2019), it is clear that statistical literacy is a major problem for Slovak 5th grade students. These facts led us to review the Singapore and Slovak curricula focusing on the display of the Data display domain, and to compare the content of education in the domain in Slovakia and Singapore with TIMSS 2015 mathematical framework.